Identifikasi Protein Plasmodium falciparum yang Tidak Berkarakter Melalui Analisis In-silico - Vianney Widjaja; Albert Lim; Benedicta Aini; Gabrielle Audrey Gandasasmita; Jeremie Theddy Darmawan; Arli Aditya Parikesit (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Background: Numerous types of research on malaria were done over a long period of time but there are still some unknowns. However, it is globally known that malaria is caused by the Plasmodium parasite, mainly and most lethally by Plasmodium falciparum. The purpose of this research is to understand the structure and function of three uncharacterized P. falciparum proteins (PF3D7_1468000, PF3D7_1147400, PF3D7_1351100) using bioinformatic methods in hopes to learn more about malaria. Methods: The three uncharacterized P. falciparum proteins were inserted into Phyre2 for knowing the protein homology, InterPro, and SUPERFAMILY hidden Markov models for understanding the domain annotation, scanprosite for knowing the post-translational modification, Ramachandran plot for protein validation, and Yasara for visualizing the protein. Results: According to the Phyre2 results, the third protein showed the highest confidence and coverage level of 100%, followed by the second protein, and the lowest was the first protein. Interpro and SUPERFAMILY results identified the first protein as WD40 repeat superfamily, the second protein as Cytochrome C subunit II-like, and the third protein as CXXC motif. Scanprosite revealed all sequences possessing protein domains in which the first protein has three protein domains, the second protein has one protein domain, and the third protein has two protein domains. According to the Ramachandran plot, the first and second protein generally has an Î±-helix structure while the third protein has an overall Î²-sheet structure, which differs to some extent from the protein structure visualization. The three protein visualizations exhibited secondary structures and more than 50 amino acid residues for each protein. Conclusion: This research concluded that the second and third uncharacterized proteins (PF3D7_1147400, PF3D7_1351100) could be promising antimalarial drug targets leading to the P. falciparum parasite death.